A comparison of the industrialization paths for Asian services outsourcing industries, and implications for poverty alleviation - F. Ted Tschang (Asian Development Bank Institute (ADBI), 2011)
This paper examines three software and/or information technology enabled services (ITES) industries - two in the early stages of development (in the People's Republic of China [PRC] and the Philippines) and one mature one (in India). Being latecomers to offshoring work, the PRC and the Philippines have developed this industry in cooperation with multinational enterprises (MNEs). PRC firms have worked with and upgraded within MNEs' value chains within the PRC market, while the Philippines has relied on MNEs to come in and set up facilities, with domestic firms setting up facilities where lower (knowledge) barriers to entry prevail. The paper also explores the ITES industries' implications for economic growth and poverty reduction. ITES industries can contribute to overall economic growth and exports, but due to their small size, will generally tend to have more observable impacts on the cities in which they are located. From the limited case data available, it appears that the ITES industries impact on overall employment and other economic sectors to varying degrees, relative to other sectors. As these industries do not help the more impoverished or less educated, they cannot be said to be a solution for the less employable or impoverished, let alone to the problem of rural poverty.
Keywords: L52; L86; O14; 330; IT-Industrie; Outsourcing; Multinationales Unternehmen; Wirtschaftswachstum; Armut; China; Indien; Philippinen